2017
DOI: 10.3389/fnmol.2016.00162
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Protein Quality Control Failure in Myelin Disorders

Abstract: Reaching the correct three-dimensional structure is crucial for the proper function of a protein. The endoplasmic reticulum (ER) is the organelle where secreted and transmembrane proteins are synthesized and folded. To guarantee high fidelity of protein synthesis and maturation in the ER, cells have evolved ER-protein quality control (ERQC) systems, which assist protein folding and promptly degrade aberrant gene products. Only correctly folded proteins that pass ERQC checkpoints are allowed to exit the ER and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
79
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 181 publications
(290 reference statements)
2
79
0
Order By: Relevance
“…The expression of heat shock proteins, including Hsp70 ( Hspa1a ) and Hsc70 ( Hspa8 ), has previously been shown to be modulated by morphine treatment of rats (Ammon-Treiber et al, 2004; Salas et al, 2011). Proper regulation of the UPR is essential for efficient myelination, as evidenced by the apparent dysregulation of UPR in multiple myelin disorders, including Charcot-Marie-Tooth disease, vanishing white matter disease, and multiple sclerosis (Lin and Popko, 2009; Volpi et al, 2017). Under normal conditions, GRP78/BiP (encoded by Hspa5) is thought to initiate the UPR by sensing misfolded proteins in the ER (Volpi et al, 2017), and its conditional ablation in OLs or Schwann cells results in cell death and severe hypomyelination (Hussien et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of heat shock proteins, including Hsp70 ( Hspa1a ) and Hsc70 ( Hspa8 ), has previously been shown to be modulated by morphine treatment of rats (Ammon-Treiber et al, 2004; Salas et al, 2011). Proper regulation of the UPR is essential for efficient myelination, as evidenced by the apparent dysregulation of UPR in multiple myelin disorders, including Charcot-Marie-Tooth disease, vanishing white matter disease, and multiple sclerosis (Lin and Popko, 2009; Volpi et al, 2017). Under normal conditions, GRP78/BiP (encoded by Hspa5) is thought to initiate the UPR by sensing misfolded proteins in the ER (Volpi et al, 2017), and its conditional ablation in OLs or Schwann cells results in cell death and severe hypomyelination (Hussien et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Proper regulation of the UPR is essential for efficient myelination, as evidenced by the apparent dysregulation of UPR in multiple myelin disorders, including Charcot-Marie-Tooth disease, vanishing white matter disease, and multiple sclerosis (Lin and Popko, 2009; Volpi et al, 2017). Under normal conditions, GRP78/BiP (encoded by Hspa5) is thought to initiate the UPR by sensing misfolded proteins in the ER (Volpi et al, 2017), and its conditional ablation in OLs or Schwann cells results in cell death and severe hypomyelination (Hussien et al, 2015). Coincidentally, Hspa5 is also the most significantly morphinerepressed gene that we detected in OLs.…”
Section: Discussionmentioning
confidence: 99%
“…MPZ itself comprises up to 50% of all myelin proteins15 and approximately 2% of all Schwann Cell transcripts during the peak of myelination 16. Normally, newly synthesized MPZ is folded and post‐translationally modified into its native conformation by ER‐protein quality control pathways (ERQC) that consist of various chaperones and other molecules 17, 18. Subsequently MPZ is processed through the Golgi, packaged into vesicles and transported to the myelin sheath 19.…”
Section: Discussionmentioning
confidence: 99%
“…While it may seem counter‐intuitive to consider this as a therapeutic strategy, translational attenuation will ultimately result in reduced levels of mutant protein in the ER which may therefore allow chaperones and foldases to better perform their normal function of proper folding and delivery of wild‐type MPZ and other myelin proteins such as PMP22 to myelin. In this situation the mutant, but not wild‐type MPZ would be degraded by ERQC pathways 23. Moreover, it has been shown that Ser63del MPZ acts as a dominant negative that also results in wild‐type MPZ retention in the ER24; as such reducing S63del translation may permit more wild‐type MPZ to be released to reach the myelin membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Myelin-forming cells of the CNS, namely oligodendrocytes, synthesize a large amount of myelin proteins and lipids and therefore are particularly susceptible to ER quality control failure (Volpi et al, 2016). Accordingly, we obtained a wider integrated overview of the molecular and biochemical pathways affected in the disease, ranging from dysregulation in cytoskeleton remodeling, ER stress, and proteasome imbalanced activity.…”
Section: Con Clus Ionsmentioning
confidence: 99%